Structure and composition of the euglossine bee community along an elevational gradient of rupestrian grassland vegetation - dos Santos, Fabíola Mendes; Beiroz, Wallace; Antonini, Yasmine; Martén-Rodríguez, Silvana; Quesada, Mauricio; Fernandes, Geraldo Wilson (Apidologie, 2020)
Euglossini is an important tribe of Neotropical bees found primarily in wet forest environments, although their distribution extends to seasonal tropical forests and mountainous grassland habitats. However, little is known about the geography and diversity of euglossine bees in mountain regions, particularly in the Brazilian semi-arid Cerrado vegetation. We evaluated the distribution of euglossine bees along an elevational gradient in Serra do Cipó, Brazil, where the vegetation varies from savanna (Cerrado) at lower elevations to rupestrian grasslands in mountain summits, and an ecotone of cerrado/rupestrian grassland at mid elevations. We also tested whether bee species richness and abundance were influenced by environmental variables (vegetation and climate) that change with elevation. Bee abundance decreased with elevation, while species richness peaked at mid elevations. Species replacement along the elevational gradient led to differences in species composition between sites; but species diversity remained relatively constant, along the gradient. Abundance and diversity patterns were similar between the dry and rainy seasons, despite differences in species composition. We emphasize the importance of preserving corridors of mesic environments in the conservation of euglossine bees for maintaining ecosystem services in mountain savannas.